Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content:1. The Role of the School Library in Achieving Cultural Development in the Light of Contemporary Technological Variables among Secondary School Students from the Teachers' Point of View in TaifCo-Prof. Eman Ibrahem Alamrity, Ms. Najah Yahya Alfaifi2. The importance of using Artificial Intelligence techniques in the fields of school learning and teachingMs. Noor Anees Karzoun3. The Effect of Using Educational Digital Images in Learning Simple Arithmetic Operations  and Conveying The Learning Effect among Students with Intellectual DisabilitiesMr. Maqbul Mohammed Hakami, Prof. Ali Mohammed Al-Shehri4. Reality of Change Leadership among Elementary School Principals in the City of Rahat  in the Negev: from the point of view of TeachersMs. Anahed Mohamed Abu Freach5. Metacognitive Beliefs as a Predictor of Mind Wandering among Taif University StudentsMs. Noor Ameer Al-Talhi* ,Prof. Sameera Mohareb Al-Otaibi6. Open-mindedness and its relationship to personality strength among university studentsAsst-Prof. Laila Najem Thajil7. The process of developing suicidal thoughts among adolescents: The social and psychological impact according to a national survey in Palestine after the Covid-19 pandemicMr. Abed Elrahman Maher Abu dalu
Keywords: Journal of Educational and Psychological Sciences